2011
DOI: 10.1007/s10298-011-0654-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella sativa fixed oil on the hormonal profile of androgens and circulating in male rats

Abstract: Eff et de l'huile fi xe de la nigelle (Nigella sativa L.) sur le profi l des androgènes chez le rat mâle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These findings are in line with previous studies [ 30 , 53 ] that concluded that TT, LH, and FSH were dramatically enhanced by Ns seed extractions. The beneficial effects of Nigella sativa extracts are owed to the boosting functioning of the hypothalamic–pituitary–testicular axis [ 54 ]. Honey supplementation during ischemia followed by reperfusion led to increased FSH, LH, and TT levels [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous studies [ 30 , 53 ] that concluded that TT, LH, and FSH were dramatically enhanced by Ns seed extractions. The beneficial effects of Nigella sativa extracts are owed to the boosting functioning of the hypothalamic–pituitary–testicular axis [ 54 ]. Honey supplementation during ischemia followed by reperfusion led to increased FSH, LH, and TT levels [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the effect of Nigella sativa oil was studied on male rat, & it was found N. sativa oil extract induced a significant increase in the weight of reproductive organs, and in the circulating levels of serum FSH, LH & testosterone as compared to control animals (P< 0.05). The study concluded that the Nigella sativa fixed oil may stimulate steroidogenesis by activation of hypothalamo-pituitarytesticular axis, (22). Recently, an Iraqi study was done to investigate the effects of Nigella sativa oil on reproductive system of rat.…”
Section: Discussionmentioning
confidence: 99%
“…El-Khasmi`s study showed that intraperitoneal injection of black seed oil in mice could increase the secretion of sex hormones (FSH, LH and Tes), a process that follows the activation of the hypothalamicpituitary-testicular axis, and then, LH is released leading to Tes biosynthesis (El Khasmi et al, 2011). Immature spermatozoa have a large amount of cytoplasm in the middle part of cells that is rich in the enzyme glucose-6-phosphate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the study of Mohamad et al showed that oral consumption of black seed increased the germ cell population and the number of mature and immature Leydig cells and also reduced cell degeneration (Mohammad et al., 2009). El‐Khasmi`s study showed that intraperitoneal injection of black seed oil in mice could increase the secretion of sex hormones (FSH, LH and Tes), a process that follows the activation of the hypothalamic‐pituitary‐testicular axis, and then, LH is released leading to Tes biosynthesis (El Khasmi et al., 2011). Immature spermatozoa have a large amount of cytoplasm in the middle part of cells that is rich in the enzyme glucose‐6‐phosphate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%